Alcohol, drug use and gambling among the Inuit of Nunavik : epidemiological profile - Muckle, Gina; Chevalier, Serge; Régie régionale de la santé et des services sociaux, Nunavik (Québec); Institut national de santé publique du Québec; Boucher, Olivier; Laflamme, Dominique; Rochette, Louis (Institut national de santé publique du Québec & Régie régionale de la santé et des services sociaux Nunavik, 2007)
Reproductions for private study or research purposes are authorized by virtue of Article 29 of the Copyright Act. Any other use must be authorized by the Government of Québec, which holds the exclusive intellectual property rights for this document. Authorization may be obtained by submitting a request to the central clearing house of the Service de la gestion des droits d’auteur of Les Publications du Québec, using the online form at http://www.droitauteur.gouv.qc.ca/en/autorisation.php or by sending an e-mail to droit.auteur@cspq.gouv.qc.ca. Yes Institut national de santé publique du Québec